2015
DOI: 10.1097/md.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Consequences of Cortical Thickness in an Asian Population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…However, close monitoring of kidney function during earlier lifespan was important since the accumulation of Aβ could start from middle age 5 . Secondly, women tended to have a greater cortical thickness than their age-matched counterpart 45,46 , and our results were in line with these findings (women vs men: + 47.7 μm, 95% CI = 21.4-74.1 μm in age-adjusted global cortical thickness). Interestingly, we found that kidney dysfunction had more prominent effects on global CTh in women (equivalent to an aging effect of 20.5 years).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, close monitoring of kidney function during earlier lifespan was important since the accumulation of Aβ could start from middle age 5 . Secondly, women tended to have a greater cortical thickness than their age-matched counterpart 45,46 , and our results were in line with these findings (women vs men: + 47.7 μm, 95% CI = 21.4-74.1 μm in age-adjusted global cortical thickness). Interestingly, we found that kidney dysfunction had more prominent effects on global CTh in women (equivalent to an aging effect of 20.5 years).…”
Section: Discussionsupporting
confidence: 81%
“…Increasing age was generally associated with less cortical thickness 4,45,46 . In our subgroup analysis, we found that in the young-old group (65-74 years-old), kidney dysfunction was significantly related to a lower global CTh, while the old-old group (≥75 years-old) also demonstrated a non-significant relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Across these studies the effect of cortical thickness varies, with some reporting relationships with executive function, processing speed, memory (59,64), whilst others reporting relationships with memory and attention (60,63). A study by Hilal et al (2015) demonstrated that WMH and microbleeds were associated with thinning in the temporal and insular regions and associated multi-domain cognitive dysfunction. The insula is an important structure with extensive connections to cortical and subcortical regions, and is involved in various processes, such as empathy, emotion, body sensation, and other aspects of social cognition (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Out of 957 subjects, 30 were diagnosed with dementia and hence were excluded from the analysis. The details of the study methodology have been described elsewhere 11. Recruitment took place from August 8, 2010 to July 24, 2015.…”
Section: Methodsmentioning
confidence: 99%